THE EFFORTS OF THE WEST JAVA PROVINCIAL GOVERNMENT IN REALIZING SDGS GOAL 5 ON GENDER EQUALITY - Vivi Pusvitasary; Shinta Julianti (Budi Luhur Journal of Strategic & Global Studies, 2026)
Abstract: This article examines the efforts of the West Java Provincial Government in realizing SDGs Goal 5 Gender Equality for the period 2018-2023 thru the perspective of intersectional feminism. This research uses a qualitative approach with a case study design on the Province of West Java and data collection techniques using literature review. The research results show 4 targets and 7 indicators set by the West Java Provincial Government. Indicator 5.1.1 under target 5.1 was achieved in 2019 and 2023. Next, under target 5.3, indicator 5.3.1 experienced fluctuating achievements, reaching the target in 2018 and 2023. As for indicator 5.5.1 under target 5.5, which is the proportion of seats occupied by women in the central parliament, regional parliament, and local government over a five-year period, it was achieved. Meanwhile, 1 target and 4 other indicators are still not satisfactory and require special attention to be achieved promptly. The efforts undertaken by the West Java Provincial Government include MOTEKAR, Sekolah Perempuan Jabar, Jabar Cekas, and Stopan Jabar.   Abstrak: Artikel ini mengkaji upaya Pemerintah Daerah Provinsi Jawa Barat dalam Mewujudkan SDGs Poin 5 Kesetaraan Gender periode tahun 2018-2023 melalui perspektif feminsme interseksionalitas. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus pada Provinsi Jawa Barat dan tehnik pengumpulan data menggunakan studi pustaka. Hasil penelitian menunjukkan 4 target dan 7 indikator yang ditargetkan oleh Pemprov Jabar, indikator 5.1.1 pada target 5.1 menunjukkan tercapai pada tahun 2019 dan 2023. Selanjutnya pada target 5.3 indikator 5.3.1 mengalami flukuasi capaian, tercapai sesuai target pada tahun 2018 dan 2023. Adapun indikator 5.5.1 dari target 5.5 yaitu Proporsi kursi yang diduduki perempuan di parlemen tingkat pusat, parlemen daerah dan pemerintah daerah dalam periode lima tahun tercapai. Sementara itu 1 Target dan 4 indikator lainnya masih belum menggembirakan dan perlu perhatian khusus untuk segera dicapai. Upaya yang telah dilakukan oleh Pemprov Jabar diantaranya MOTEKAR, Sekolah Perempuan Jabar, Jabar Cekas, dan Stopan Jabar.